HARNESSING POWER FOR PROGRESS: ANALYSING PAKISTAN’S ELECTRIC TRANSMISSION SECTOR, ITS ROLE IN ENERGY SECURITY AND ECONOMIC STABILITY (2018–2023) - Majid Mohsin; Dr. Syedah Sadia Kazmi; Muhammad Shakil Jan (Journal of Religion and Society, 2025)
This paper examines the role of Pakistan’s electric transmission sector in ensuring energy security, driving economic stability and supporting national security from 2018 to 2023. Employing a convergent mixed-methods design, the study integrates qualitative insights from interviews and surveys with quantitative data from field observations, NEPRA (National Electric Power Regulatory Authority) reports and case studies. The findings reveal that inefficiencies within the transmission sector, including high transmission and distribution (T&D) losses, technical issues, aging infrastructure and governance challenges, have far-reaching implications for the country’s energy and economic landscapes. Quantitative analysis shows that T&D losses consistently exceed 18% annually, resulting in substantial financial losses and contributing to the circular debt crisis, which has surpassed PKR 2.3 trillion. Qualitative insights from experts and policymakers highlight operational bottlenecks, inadequate investments and policy ambiguities as persistent barriers to improvement. These inefficiencies disrupt energy supply, deter industrial growth and escalate production costs, leading to reduced GDP growth and diminished export competitiveness. The paper also identifies the critical role of the transmission sector in national security and geopolitical tensions. Proposed strategies include modernizing infrastructure, integrating renewable energy sources, implementing advanced metering technologies and introducing governance reforms. Keywords:Energy Security, Economic Security, Sustainable Growth, Peace and Prosperity, Energy Policy